A 23.3 dBm CMOS power amplifier with third-order gm cancellation linearization technique achieving OIP3 of 34 dBm. Issue 2 (22nd February 2021) - Mariappan, Selvakumar; Rajendran, Jagadheswaran; Mohd Noh, Norlaili; Yusof, Yusman; Kumar, Narendra
Abstract : Purpose: The purpose of this paper is to implement a highly linear 180 nm complementary metal oxide semiconductor (CMOS) power amplifier (PA) to meet the stringent linearity requirement of an long term evolution (LTE) signal with minimum trade-off to power added efficiency (PAE). Design/methodology/approach: The CMOS PA is designed in a cascaded dual-stage configuration comprises a driver amplifier and a main PA. The gate voltage (VGS) of the driver amplifier is tuned to optimize its positive third-order transconductance (gm3 ) to be canceled with the main PA's fixed negative gm3 . The gm3 cancellation between these stages mitigates the third-order intermodulation product (IMD3) that contributes to enhanced linearity. Findings: For driver's VGS of 0.82 V with continuous wave signal, the proposed PA achieved a power gain of 14.5 dB with a peak PAE of 31.8% and a saturated output power of 23.3 dBm at 2.45 GHz. A maximum third-order output intercept point of 34 dBm is achieved at 20.2 dBm output power with a corresponding IMD3 of −33.4 dBc. When tested with a 20 MHz LTE signal, the PA delivers 19 dBm maximum linear output power for an adjacent channel leakage ratio specification of −30 dBc. Originality/value: In this study, a novel cascaded gm3 cancellation technique has been implemented to achieve a maximum linear output power under modulated signals.